Do Surgical Times Moderate the Association Between Clinical Risk Factors and Wound Complications After Cesarean Delivery? [255]. (May 2015) - Sharma, Ruchira; Bauer, Alison Marie; Lappen, Justin Ross; Hackney, David Nicholas
Abstract : INTRODUCTION: Several risk factors for postoperative wound complications could potentially operate through a modification of surgical times. For example, if obesity both increases the risk of wound complications and increases surgical times, the association between obesity and wound complications could be modified through increased surgical times. METHODS: We performed a secondary analysis of maternal-fetal medicine units network trial of labor after cesarean delivery (TOLAC) database, a prospective cohort of women undergoing TOLAC between 1999 and 2002. Participants were included if they underwent unscheduled cesarean deliveries without major congenital anomalies and had complete data. Linear regression with backward stepwise elimination was used to identify variables potentially associated with total operative time. To determine the potential presence of a moderation effect, logistic regression was then used with wound complications as the outcome variable and predictor variables of surgical time, the variables that were associated with surgical time in the linear regression model and interaction variables followed by stepwise elimination. The logistic regression was also stratified by operative time quartile. RESULTS: A total of 27, 376 participants met the inclusion criteria. Variables associated with total surgical time in the final model included body mass index, number of prior cesarean deliveries, uterine and skin incision type, nonurgent delivery indications, and singleton gestation. These variables plus operative time and interaction variables were then evaluated as predictors of wound complications. After stepwise elimination, the interaction between obesity and surgical time was significant ( P =.01), although the individual variables were not. In a regression model stratified by surgical time, the association between obesity and several other clinical predictors was only significant in the 25–50% quartile (odds ratio 3.66, P <.001). CONCLUSION: The association between obesity and wound complications is significantly moderated by surgical times. Thus, it appears that the increased risk of wound complications secondary to obesity can potentially be decreased by maintaining short operative times and at very long operative times the additional increased risk posed by obesity may be negligible.